Neurocognitive and functional performance in psychotic and non-psychotic bipolar patients and schizophrenia patients - Aparicio, A.; Sánchez-Morla, E.M.; Santos, J.L. (European psychiatry, 2016)
It has been suggested that psychotic bipolar patients have more severe cognitive deficits and lower functioning that non-psychotic bipolar patients. To evaluate neurocognitive and functional performance in stabilized psychotic bipolar patients (BP+), non-psychotic bipolar patients (BP−) and schizophrenia patients (SZ). To examine whether BP+ might be defined as a more homogenous subtype of bipolar disorder with more severe cognitive deficit and more severe functional impairment. Fifty TB+, 50 TB−, 50 SZ and 51 controls were evaluated with a comprehensive neurocognitive battery (WCST, FAS, TMT-A and B, Stroop Test, Digits span, letters and numbers – WMS-III−, CVLT, ROCFT, CPT-DS). Moreover, patients were evaluated with clinical scales (PANSS, MADRS, YMRS) and functionality scales (WHOs Disability Assessment Scales, QLS and GAF). IBM SPSS Statistics (version 19.0) was used to the data analysis. No significant differences were found between three patients’ samples (P<0.0001). No significant differences in neurocognitive measures were found between BP+ and BP−. Significant differences were found between both groups of bipolar patients and schizophrenia in working memory measures (P<0.0001). BP+ and BP− showed significant higher functionality than SZ (P<0.0001), without significant differences in functionality between BP+ and BP−. The pattern of neurocognitive and functional deficit is similar in BP+ and BP−. The neurocognitive deficit is very similar in both groups of bipolar patients groups in comparison to SZ; functionality is better in both bipolar groups than in schizophrenia patients.